Novel approaches to define responders to interventional treatment in hypertension: insights from the SPYRAL HTN-OFF and HTN-ON MED trials - Schmieder, Roland; Hettrick, Douglas A.; Böhm, Michael; Kandzari, David E.; Kario, Kazuomi; Mahfoud, Felix; Tsioufis, Konstantinos; Weber, Michael A.; Esler, Murray D.; Townsend, Raymond R. (Hypertension Research, 2025)
Multiple sham-controlled clinical trials have demonstrated significant reductions in both office and 24-h blood pressure (BP) following radiofrequency renal denervation (RDN) in the uncontrolled hypertension population. Notably, the blood pressure response varies widely within individual participants, thus showing a clinical need to identify potential RDN “responders” prior to the procedure. Despite multiple analytic efforts, no single parameter, aside from baseline blood pressure, has been consistently associated with BP reduction following RDN. However, this failure may be due to limitations in empiric definitions of responders. Indeed, commonly applied responder definitions based on the difference between two point-in-time BP measurements are fraught due to visit-to-visit variability in office and 24-h blood pressure endpoints. Several factors should be considered to develop a more clinically useful operational definition of procedural response including relative changes in office and 24-h BP, consideration of the temporal response to RDN, as well as adjustment for baseline BP. The current evidence may provide incentives for future expert consensus to precisely define responders to hypertension treatments. (Figure presented.)
CRIS-Team Scopus Importer:2024-11-22
Keywords: Blood pressure variability; Renal denervation; Responders